Origin, distribution, and function of three frequent coding polymorphisms in the gene for the human P2X7 ion channel - Schäfer, Waldemar; Stähler, Tobias; Pinto Espinoza, Carolina; Danquah, Welbeck; Knop, Jan Hendrik; Rissiek, Björn; Haag, Friedrich; Koch-Nolte, Friedrich (Frontiers in Pharmacology, 2022)
P2X7, an ion channel gated by extracellular ATP, is widely expressed on the plasma membrane of immune cells and plays important roles in inflammation and apoptosis. Several single nucleotide polymorphisms have been identified in the human P2RX7 gene. In contrast to other members of the P2X family, non-synonymous polymorphisms in P2X7 are common. Three of these occur at overall frequencies of more than 25% and affect residues in the extracellular "head"-domain of P2X7 (155 Y/H), its "lower body" (270 R/H), and its "tail" in the second transmembrane domain (348 T/A). Comparison of the P2X7 orthologues of human and other great apes indicates that the ancestral allele is Y - R - T (at 155 - 270 - 348). Interestingly, each single amino acid variant displays lower ATP-sensitivity than the ancestral allele. The originally published reference sequence of human P2X7, often referred to as "wildtype", differs from the ancestral allele at all three positions, i.e. H - H - A. The 1000 Genome Project determined the sequences of both alleles of 2500 human individuals, including roughly 500 persons from each of the five major continental regions. This rich resource shows that the ancestral alleles Y155, R270, and T348 occur in all analyzed human populations, albeit at strikingly different frequencies in various subpopulations (e.g. 25-59% for Y155, 59-77% for R270, and 13-47% for T348). BLAST analyses of ancient human genome sequences uncovered several homozygous carriers of variant P2X7 alleles, possibly reflecting a high degree of inbreeding, e.g. H - R - T for a 50.000 year old Neanderthal, H - R - A for a 24.000 year old Siberian, and Y - R - A for a 7.000 year old mesolithic European. In contrast, most present-day individuals co-express two copies of P2X7 that differ in one or more amino acids at positions 155, 270 and 348. Our results improve the understanding of how P2X7 structure affects its function and suggest the importance of considering P2X7 variants of participants when designing clinical trials targeting P2X7.